1999
DOI: 10.1515/reveh.1999.14.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Air Pollution and Asthma: A Review of Epidemiological and Biological Studies

Abstract: The link between exposure to air pollution and exacerbation of asthma symptoms has been investigated by epidemiological study and by direct biological experimentation. In asthmatics, epidemiological studies generally show a positive correlation between the particulate fraction of air pollution and increased morbidity, although roles for other co-pollutants (for example, ozone) are implicated as well. Direct experimentation using air pollutants, especially particles, to investigate their effects on humans or on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 48 publications
(1 reference statement)
1
24
0
Order By: Relevance
“…6,8,25,213,305,308, Recent reviews discuss the toxicologic and epidemiologic evidence for health risks from gasoline and diesel engine emissions; 324,349 the toxicology of ultrafine anthropogenic atmospheric aerosols; 345 and the relationship of particle air pollution to asthma. 350 The proceedings of recent conferences are sources of more detailed coverage of current health-related research. 351,352 Epidemiology Epidemiology, the medical science that investigates the quantitative factors controlling the frequency and distribution of disease, provided the initial evidence that the PM 10 ambient air standard did not meet the legal criteria in the Clean Air Act to "protect the public health" while "allowing an adequate margin of safety."…”
Section: Particle Health Effect Researchmentioning
confidence: 99%
“…6,8,25,213,305,308, Recent reviews discuss the toxicologic and epidemiologic evidence for health risks from gasoline and diesel engine emissions; 324,349 the toxicology of ultrafine anthropogenic atmospheric aerosols; 345 and the relationship of particle air pollution to asthma. 350 The proceedings of recent conferences are sources of more detailed coverage of current health-related research. 351,352 Epidemiology Epidemiology, the medical science that investigates the quantitative factors controlling the frequency and distribution of disease, provided the initial evidence that the PM 10 ambient air standard did not meet the legal criteria in the Clean Air Act to "protect the public health" while "allowing an adequate margin of safety."…”
Section: Particle Health Effect Researchmentioning
confidence: 99%
“…It stretches for about 120 km along the banks of the Nile. There is considerable evidence linking increased levels of air pollution to adverse effects on human health [1,2]. Egypt is littered with garbage, pollution and people who do not care about their country.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have shown adverse effects of ambient air pollution on respiratory health (9,10) and increased risk of atopic diseases and allergic sensitization when children are exposed to ambient particulate matter (11). Among these pollutants, diesel exhaust particles (DEP) are important components of the pollution respirable particles in the range of 2.5 μ m or less.…”
Section: Introductionmentioning
confidence: 99%